Düzeltme: YÖK Atlas Verilerine Göre Gastronomi ve Mutfak Sanatları Bölümlerinin Değerlendirilmesi: Ege Bölgesi Örneği - Şimşek, Aykut; Solmaz, Rıdvan; Güleç, Enes (Gülay BULGAN, 2021)
In this study, based on YÖK Atlas data, an evaluation was made on Gastronomy and Culinary Arts Departments in universities in the Aegean Region in 2019. With this study, it is aimed to analyze the students who are placed in the Gastronomy and Culinary Arts Departments of these universities in a statistical and systematic way. In the research, document review, which is one of the qualitative research methods, was carried out based on the scanning model. The research included findings regarding the gender of the students, their geographical regions, educational status, high school areas they graduated, YKS success rankings, general preference trends, the same or different program preference trends and the programs in the preference lists. As a result of the research the number of female students enrolled in the gastronomy and culinary arts department in the Aegean region is less than the number of male students. It was determined that the students come from the Aegean region the most, the majority of the students pass through general high school programs that are 'no discrimination of fields', and different programs are preferred in the preferences of the majority of students. It has been determined that the students mostly come from the Aegean Region. When the YKS success rankings were examined, it was observed that İzmir Kâtip Çelebi University had the highest success ranking, while Kütahya Dumlupınar University had the lowest success ranking. It has been determined that the majority of the placed students include different programs in their preferences.The original article was published on 31 December 2020. https://dergipark.org.tr/en/pub/ijgtr/issue/59452/749963
Keywords: Tourism (Other); Turizm (Diğer)